Εκτιμήσεις της οικιακής ζήτησης ενέργειας στην Ελλάδα την περίοδο 1970-2003 - Πολέμης Μιχαήλ Λ. (SPOUDAI Journal of Economics and Business, 2007)
This paper with the title “Assessment of residential energy demand in Greece during the period 1970-2003 attempts to cast light on the main determinants of residential energy demand in Greece. For this purpose we used cointegration analysis in order to capture short-run and longrun effects of oil and electricity demand respectively. From the empirical analysis that spans the period 1970-2003, we find that in the long-run oil and electricity demand appears to be income elastic and price inelastic respectively. We also find that natural gas, which is taken into account through the inclusion of a broken trend (1997-2003), appears to affect energy demand and thus the magnitude of the relevant elasticities. JEL Classifications: O38; Q4